Labour migration from the eastern partnership countries: Evolution and policy options for better outcomes - Luca Barbone; Mikhail Bonch-Osmolovsky; Matthias Lücke (Center for Social and Economic Research (CASE), 2013)
This study is part of the project entitled Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Countries for the European Commission1. The study was written by Luca Barbone (CASE) Mikhail Bonch- Osmolovskiy (CASE) and Matthias Luecke (Kiel). It is based on the six country studies for the Eastern Partnership countries commissioned under this project and prepared by Mihran Galstyan and Gagik Makaryan (Armenia), Azer Allahveranov and Emin Huseynov (Azerbaijan), Aleksander Chubrik and Aliaksei Kazlou (Belarus), Lasha Labadze and Mirjan Tukhashvili (Georgia), Vasile Cantarji and Georgeta Mincu (Moldova), Tom Coupé and Hanna Vakhitova (Ukraine). The authors would like to thank for their comments and suggestions Kathryn Anderson, Martin Kahanec, Costanza Biavaschi, Lucia Kurekova, Monica Bucurenciu, Borbala Szegeli, Giovanni Cremonini and Ummuhan Bardak, as well as the dbaretailed review provided by IOM. The views in this study are those of the authors' only, and should not be interpreted as representing the official position of the European Commission and its institutions.
Keywords: F22; F24; D78; I25; J15; J83; J01; J40; J61; 330; Labour economics; Labour markets; Labour mobility; ENPI; EU; Eastern Partnership; Armenia; Azerbaijan; Belarus; Georgia; Moldova; Ukraine